Management Development in Multiple Meaningful Phrasemas - Davronbek Abdullaev (Genius Journals, 2022)
In scientific sources, the phrase has been recognized to add clarity, brilliance, expressiveness, color, and uniqueness to speech. Rather, the enchanting nature of artistic observation is the degree to which language is elaborated, i.e., the perfection of expression determines the nature of the phrasal verb. Consequently, stable lexical units serve as a stepping stone from a common style of speech to a creative interpretation. Thus, the concept generalizes the integrity of the speech-linguistic relationship. It combines a change of meaning, a vital basis, and a linguistic relationship.
Keywords: meaning; relationship; integrity; brilliance